Meaning in Life: A Major Predictive Factor for Loneliness Comparable to Health Status and Social Connectedness - Macià, Dídac; Cattaneo, Gabriele; Solana, Javier; Tormos, José M.; Pascual-Leone, Alvaro; Bartrés-Faz, David (Frontiers in Psychology, 2021)
Objective: Loneliness is the subjective distress of feeling alone and has a strong impact on wellbeing and health. In addition to well-known predictors like isolation and poor health, a better understanding of the psychological determinants of loneliness would offer effective targets for future complementary interventions. Methods: In this cross-sectional observational study (N = 2,240), we compared the explanatory power of several important risk factors of loneliness with the affective, motivational, and cognitive aspects of the Meaning in Life (MiL) construct. Different nested linear models were compared including socio-demographic, lifestyles, social-connectedness, and self-rated health variables, to assess the overlapping and non-overlapping explanatory power of each of them. Results: Health status and MiL were found to be the most important predictors of loneliness, followed by social connectedness and, with a much lower weight, lifestyles, and socio-demographic factors. Within the MiL factor, the most cognitive component, sense of coherence, had a greater explanatory power than the more affective and motivational ones. Conclusion: Reduced MiL, the capacity of an individual to attach “value and significance” to life, is a crucial predictor to the feeling of loneliness. These results suggest that programs aiming to combat loneliness should go well beyond situational interventions and include more cognitive, value-centered interventions that enable individuals to define and pursue a meaningful vital plan.